Assessment of Informal Settlements Using Geospatial Techniques: A Case of Adama City, Oromia, Ethiopia - Daryos, Berhanu (ASTU, 2024)
In less developed nations, the recent rapid expansion of urban areas is frequently linked with the emergence of informal settlements, which can exacerbate social and environmental issues and hinder sustainable development. Consequently, evaluating informal settlements becomes crucial for effective management and future success. This research will concentrate on assessing informal settlements in Adama City, Oromia, Ethiopia, using geospatial techniques. The investigation will explore the application of geospatial methodologies to comprehend and map informal settlements within the specific urban context. The likely inclusion of google earth imagery, Orthophoto, Geographic Information Systems (GIS), and related tools will facilitate the analysis of spatial patterns, characteristics, and dynamics of informal settlements in Adama City. The analysis starts by identifying globally accepted indicators and analyzing the pattern, extent and rate of Adama city illegal settlement and then modeling the future controlling system using conceptual and logical modeling. The result shows the maps and models created to show Adama city informal settlement information in order to control, plan and redesign the advanced and standardized land use land cover. Therefore, the findings of this study are important in re- designing operation of the future Adama city land use intent to develop comprehension, updated, secured, reliable, and complete land use information.
Keywords: Informal Settlements, Geospatial Technologies, Spatial pattern, extent and rate